Detection and isolation of Shiga Toxin‐producing Escherichia coli (STEC) strains in caecal samples from pigs at slaughter in Italy. Issue 3 (23rd May 2019) - Arancia, Silvia; Iurescia, Manuela; Lorenzetti, Serena; Stravino, Fiorentino; Buccella, Carmela; Caprioli, Andrea; Franco, Alessia; Battisti, Antonio; Morabito, Stefano; Tozzoli, Rosangela
Abstract: Shiga toxin‐producing Escherichia coli (STEC) strains are food‐borne pathogens of public health concern. Despite ruminants are the most important reservoir, STEC human infections have also been attributed to pigs. We examined for the presence of STEC in 234 samples of swine caecal content collected during the year 2015 at Italian abattoirs in the framework of the harmonized monitoring of antimicrobial resistance (Decision 2013/652/EU). The presence of stx genes was detected in 122 (52.1%) samples, which were subsequently subjected to STEC isolation and characterization. The analysis of the 66 isolated STEC strains showed that the majority of the isolates (74.2%) possessed the stx2a gene subtype, in a few cases (16.7%) in combination with stx2b or stx2c . Only 25.8% of isolates possessed the stx2e subtype, typical of swine‐adapted STEC. None of the isolates possessed the intimin‐coding eae gene and the majority of them did not belong to serogroups commonly associated with human infections. The results of this study suggest that pigs can be considered as potential reservoir of certain STEC types. Abstract : Shiga toxin‐producing Escherichia coli (STEC) strains are food‐borne pathogens of public health importance. Ruminants are the most important reservoir, but STEC human infections have also been attributed to pigs. A high prevalence of STEC was identified in the caecal content of pigs at slaughter in Italy. Most of the isolated STEC possessed the stx2a gene subtype but were negative for the presence of accessory virulence genes as the intimin‐coding eae gene. The remaining isolates possessed the stx2e, typical of swine‐adapted STEC. The results of this study suggest that pigs can be considered as potential reservoir of certain STEC types, which may be carried along the food production chain.